A Functional Network of Novel Barley MicroRNAs and Their Targets in Response to Drought - Aleksandra Smoczynska (Genes, 2020)
The regulation of mRNA (messenger RNA) levels by microRNA-mediated activity is especially important in plant responses to environmental stresses. In this work, we report six novel barley microRNAs, including two processed from the same precursor that are severely downregulated under drought conditions. For all analyzed microRNAs, we found target genes that were upregulated under drought conditions and that were known to be involved in a plethora of processes from disease resistance to chromatin–protein complex formation and the regulation of transcription in mitochondria. Targets for novel barley microRNAs were confirmed through degradome data analysis and RT-qPCR using primers flanking microRNA-recognition site. Our results show a broad transcriptional response of barley to water deficiency conditions through microRNA-mediated gene regulation and facilitate further research on drought tolerance in crops.